2011
DOI: 10.1152/ajpcell.00099.2011
|View full text |Cite
|
Sign up to set email alerts
|

Real-time observation of flow-induced cytoskeletal stress in living cells

Abstract: The mechanical stress due to shear flow has profound effects on cell proliferation, transport, gene expression, and apoptosis. The mechanisms for flow sensing and transduction are unclear, but it is postulated that fluid flow pulls upon the apical surface, and the resulting stress is eventually transmitted through the cytoskeleton to adhesion plaques on the basal surface. Here we report a direct observation of this flow-induced stress in the cytoskeleton in living cells using a parallel plate microfluidic chip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 39 publications
5
53
1
Order By: Relevance
“…17 Photosynthesis decreases for both stomatal (g s ) and non-stomatal inhibition (A), as already observed on tomato. 16 While photosynthesis being compromised in both species, from the comparison between the two species emerged a greater capacity of purple coneflower in the 120-min treatments to maintain the stomata opened, continuing to exchange CO 2 with the water vapor.…”
Section: Gas Exchangesupporting
confidence: 63%
“…17 Photosynthesis decreases for both stomatal (g s ) and non-stomatal inhibition (A), as already observed on tomato. 16 While photosynthesis being compromised in both species, from the comparison between the two species emerged a greater capacity of purple coneflower in the 120-min treatments to maintain the stomata opened, continuing to exchange CO 2 with the water vapor.…”
Section: Gas Exchangesupporting
confidence: 63%
“…Cells withstand mechanical loading through support from cytoskeleton, a heterogeneous, anisotropic collection of dynamically cross-linked structural proteins. [41][42][43][44][45] The deformation of a cell depends on the intrinsic elastic deformation of fibrous cytoskeletal proteins and plastic deformation involving dynamics of reversible cross-linking and cytoskeleton reorganization. 46,47 Slow shear loading engages the plastic processes that significantly modify the local force around the Ca 2 + transducers acting like dashpots in series with the transducer.…”
Section: Discussionmentioning
confidence: 99%
“…The device was fabricated using soft lithography following the fabrication process described previously. 27 For inlet and outlet, holes were punched through the PDMS at the ends of the chamber. The chip was mounted on a home-made assembly that allowed fluorescence imaging.…”
Section: Flow Chamber and Pressure Servo Pumpmentioning
confidence: 99%
“…Time-dependent stresses in single molecules have been measured with atomic-force microscopy (AFM), laser traps and force-sensitive fluorescent Förster resonance energy transfer (FRET) probes (Bustamante et al, 2004;Cornish and Ha, 2007;Meng et al, 2011;Meng and Sachs, 2011a;Meng and Sachs, 2011b). AFM and laser traps can measure the mechanics of single molecules in vitro, but FRET probes function in vivo and in vitro and experiments using these probes have revealed that all filamentous proteins in a cell seem to be under resting tension (Grashoff et al, 2010;Brenner et al, 2011;Meng and Sachs, 2011b;Rahimzadeh et al, 2011;Wang et al, 2011;Meng and Sachs, 2012). If proteinaceous fibers are to be used for signaling, it is important that resting tension is maintained (Ingber, 2008) because fibers under tension can transmit signals close to the speed of sound (Na et al, 2008).…”
Section: The Energy Involved In Mechanical Transductionmentioning
confidence: 99%